2014
DOI: 10.1152/ajpendo.00287.2014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for fatty acids mediating CL 316,243-induced reductions in blood glucose in mice

Abstract: MacPherson RE, Castellani L, Beaudoin M, Wright DC. Evidence for fatty acids mediating CL 316,243-induced reductions in blood glucose in mice. Am J Physiol Endocrinol Metab 307: E563-E570, 2014. First published August 5, 2014; doi:10.1152 doi:10. /ajpendo.00287.2014, a ␤ 3-adrenergic agonist, was developed as an antiobesity and diabetes drug and causes rapid decreases in blood glucose levels in mice. The mechanisms mediating this effect have not been fully elucidated; thus, the purpose of the current study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 36 publications
9
38
1
Order By: Relevance
“…In the present study, where beta adrenergic stimulation is being exogenously provided, this potential confounding issue would likely be avoided. In fact, we have previously shown that CL-mediated increases in plasma glycerol and fatty acid release are intact in IL-6 À/À mice suggesting that beta adrenergic signaling in adipose tissue is normal in these animals (MacPherson et al 2014).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, where beta adrenergic stimulation is being exogenously provided, this potential confounding issue would likely be avoided. In fact, we have previously shown that CL-mediated increases in plasma glycerol and fatty acid release are intact in IL-6 À/À mice suggesting that beta adrenergic signaling in adipose tissue is normal in these animals (MacPherson et al 2014).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, we have previously shown that CL‐mediated increases in plasma glycerol and fatty acid release are intact in IL‐6 −/− mice suggesting that beta adrenergic signaling in adipose tissue is normal in these animals (MacPherson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; MacPherson et al . ), serum non‐esterified fatty acids (NEFA) and glycerol concentrations were determined on a 96‐well plate measured using commercially available kits (NEFA: Wako Diagnostics, Richmond, VA; Glycerol: Sigma‐Aldrich, Oakville, ON, Canada). Serum creatine kinase was measured using a kit from Pointe Scientific (Canton, MI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Nonesterified fatty acids (NEFA; Wako Diagnostics) and glycerol (cat no. F6428; Sigma Aldrich) were measured on a 96well plate as previously described (MacPherson, Castellani, Beaudoin, & Wright, 2014). Glucagon and insulin were measured via enzyme-linked immunosorbent assays (ELISA) (cat no.…”
Section: Serum Measurementsmentioning
confidence: 99%